(untitled) (Al-Farooq Journal of Sciences, 2026)
The world is witnessing a rapid digital transformation as a result of successive advancements in information and communication technologies. This has prompted higher education institutions to adopt e-government as a key approach to developing institutional performance and improving the quality of academic and administrative services. In this context, this study aimed to identify the impact of digital infrastructure and the proficiency of technical skills on the implementation of e-government at the University of Tripoli. This was achieved by surveying faculty members’ opinions on its current application and requirements. The study employed a descriptive-analytical methodology, utilizing a questionnaire as the primary tool for data collection and analysis. The results showed a high level of e-government implementation at the University of Tripoli, with a mean score of 4.35 and a standard deviation of 0.45. This reflects the availability of supportive elements for implementing e-government and underscores the pivotal importance of digital infrastructure and technical skills in enhancing the efficiency of administrative processes and supporting digital transformation within the university. In light of these findings, the study recommended continued investment in developing digital infrastructure, updating administrative systems and applications, enhancing cybersecurity and data governance, and developing the digital skills of staff and faculty through specialized training programs. It also emphasized the importance of attracting qualified professionals in e-government and digital transformation. Furthermore, the study stressed the need for sustainable strategic plans to address technical and organizational challenges, thereby contributing to a more efficient and flexible university administration and supporting the move towards a smart university and sustainable digital transformation.